2005
DOI: 10.1249/01.mss.0000181302.97948.90
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Physical Activity among Pregnant Women in the United States

Abstract: Many pregnant women do not appear to be meeting the physical activity recommendations. Healthcare providers should further encourage the promotion of physical activity during uncomplicated pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
120
7
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(151 citation statements)
references
References 14 publications
22
120
7
2
Order By: Relevance
“…The association between manual occupation and lower levels of physical inactivity was expected, given the nature of the job function. The association between level of physical activity and marital status has been observed by previous studies 68 .…”
Section: Discussionsupporting
confidence: 69%
“…The association between manual occupation and lower levels of physical inactivity was expected, given the nature of the job function. The association between level of physical activity and marital status has been observed by previous studies 68 .…”
Section: Discussionsupporting
confidence: 69%
“…We also found that increasing income, being nulliparous and a worker was associated with a decreased time spent at home. Several others have reported the same factors as being associated with increased physical activity among pregnant women (Ning et al, 2003;Petersen et al, 2005;Schmidt et al, 2006) which suggests an inverse relationship between our measure of time spent at home and physical activity measures in other studies. These were all cross-sectional studies using various methods: self-reported activities based on an interview at time of birth, 24-h recall diaries during each trimester and a random sample of the population from a behavioral risk factors surveillance system.…”
Section: Discussionsupporting
confidence: 60%
“…Pregnancy is a life event that seems to support sedentary behaviours (44,45) . Although physical activity can be a protective factor for many pregnancy related disorders, this research indicates that too few pregnant women are sufficiently active (31) .…”
Section: Physical Activity Behaviourmentioning
confidence: 99%